2018
DOI: 10.1038/s41598-018-23486-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of human swallowing using a simple motion tracking system

Abstract: The number of patients with dysphagia is rapidly increasing due to the ageing of the population. Therefore, the importance of objectively assessing swallowing function has received increasing attention. Videofluoroscopy and videoendoscopy are the standard clinical examinations for dysphagia, but these techniques are not suitable for daily use because of their invasiveness. Here, we aimed to develop a novel, non-invasive method for measuring swallowing function using a motion tracking system, the Kinect v2 sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…In addition, we confirmed that the detected swallowing onset time was consistent with water swallowing, not saliva swallowing, using a video recorded by our newly developed simple swallow-tracking system (Hashimoto et al, 2018) (Supporting Fig. S1C).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…In addition, we confirmed that the detected swallowing onset time was consistent with water swallowing, not saliva swallowing, using a video recorded by our newly developed simple swallow-tracking system (Hashimoto et al, 2018) (Supporting Fig. S1C).…”
Section: Resultssupporting
confidence: 68%
“…S1A, S1B). Additionally, we confirmed that the changes in impedance and sounds corresponded to water swallowing by using the video captured by our simple swallow-tracking system (SSTS) (Hashimoto et al, 2018). We inserted swallowing triggers, which corresponded to the swallowing onset time, into the ECoG data.…”
Section: Signal Segmentation Based On Swallowing-related Events Swalsupporting
confidence: 57%
See 2 more Smart Citations
“…Dysphagia, characterised by a difficulty in swallowing, is a complication associated with several conditions, including stroke, dementia and neurological disorders [ 1 ]. An ageing population means there is an increased interest in this condition [ 2 , 3 ]. Without treatment, dysphagia can lead to food avoidance, particularly in the elderly, which may result in serious consequences such as nutritional and respiratory complications, and even death [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%